Pattern recognition algorithm to identify detrusor overactivity on urodynamics - Wang, Hsin‐Hsiao Scott; Cahill, Dylan; Panagides, John; Nelson, Caleb P.; Wu, Hau‐Tieng; Estrada, Carlos (Neurourology and urodynamics, 2021)
Aims Detrusor overactivity (DO) of the bladder is a finding on urodynamic studies (UDS) that often correlates with lower urinary tract symptoms and drives management. However, UDS interpretation remains nonstandardized. We sought to develop a mathematical model to reliably identify DO in UDS. Methods We utilized UDS archive files for studies performed at our institution between 2013 and 2019. Raw tracings of vesical pressure, abdominal pressure, detrusor pressure, infused volume, and all annotations during UDS were obtained. Patients less than 1 year old, studies with calibration issues, or those with significant artifacts were excluded. In the training set, five representative DO patterns were identified. Candidate Pdet signal segments were matched to representative DO patterns. Manifold learning and dynamic time warping algorithms were used. Five‐fold cross validation (CV) was used to evaluate the performance. Results A total of 799 UDS studies were included. The median age was 9 years (range, 1–33). There were 1,742 DO events that did not overlap with annotated artifacts (cough, cry, valsalva, movements). The AUC of the training sets from the five‐fold CV was 0.84 ± 0.01. The five‐fold CV leads to an overall accuracy 81.35%, and sensitivity and specificity of detecting DO events are 76.92% and 81.41%, respectively, in the testing set. Conclusions Our predictive model using machine learning algorithms provides promising performance to facilitate automated identification of DO in UDS. This would allow for standardization and potentially more reliable UDS interpretation. Signal processing and machine learning interpretation of the other components of UDS are forthcoming.